The similarity regime for natural convection in a vertical cylindrical well filled with an anisotropic porous medium - DEGAN, GÉRARD; GIBIGAYE, ADAM MOHAMED; AKOWANOU, CHRISTIAN DJIDJOHO; AWANOU, C. NORBERT (My University, 2008)
An integral method based on Lighthill’s analysis (Q J Mech Appl Math 6 (1953) 398–439) is carried out to study the similarity regime for penetration of convective heat transfer in a vertical cylindrical well filled with an anisotropic porous medium. The porous medium is anisotropic in permeability with its principal axes oriented in a direction that is oblique to the gravity vector. In the limit of the slenderness of the porous matrix, the penetration length of the convective flow and the heat-transfer rate are expressed in terms of the anisotropic properties of the porous medium, the modified Darcy–Rayleigh number and the aspect ratio of the geometrical configuration. A scale analysis is applied to predict the order of magnitudes involved in the similarity regime of the phenomenon. The conditions of existence of the similarity pattern is found to be dependent on the anisotropic parameters. It is demonstrated that both the anisotropic permeability ratio and the orientation angle of the principal axes have a strong influence on the heat-transfer rate and on the vertical penetration length into the well.
Keywords: Anisotropic porous mediumConvectionDarcy–Rayleigh numberPenetrative flows